1998
DOI: 10.1021/je980037n
|View full text |Cite
|
Sign up to set email alerts
|

Vapor−Liquid Equilibria for the Hexane + Hexadecane and Hexane + 1-Hexadecanol Systems at Elevated Temperatures and Pressures

Abstract: Vapor and liquid equilibrium compositions have been measured for the hexane + hexadecane and the hexane + 1-hexadecanol systems at temperatures from 472.0 K to 623.0 K and pressures from 6.2 bar to 46.4 bar. A continuous-flow apparatus was used both to minimize possible thermal degradation and to accurately measure the lower hexadecanol concentrations in the vapor phase. Mixture critical pressures and compositions were also measured. Results indicate that the addition of the hydroxyl group to the C 16 hydrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Therefore, it is concluded that equilibrium conditions were present for all binary systems that were measured. These results have also been reported in the open literature Thies, 1997, 1998;Joyce et al, 1998Joyce et al, , 1999aJoyce et al, , 1999b. Considering all sources of error, the reported liquid and vapor compositions are accurate to better than ±3 and ±4% deviation in the minor component, respectively.…”
Section: Det025supporting
confidence: 86%
“…Therefore, it is concluded that equilibrium conditions were present for all binary systems that were measured. These results have also been reported in the open literature Thies, 1997, 1998;Joyce et al, 1998Joyce et al, , 1999aJoyce et al, , 1999b. Considering all sources of error, the reported liquid and vapor compositions are accurate to better than ±3 and ±4% deviation in the minor component, respectively.…”
Section: Det025supporting
confidence: 86%
“…19 Prediction of critical lines for different n-hexane + n-alkane binary systems, with the RKPR EOS and correlations developed in this work. Experimental data from [32][33][34]. …”
Section: The Binary Series Of Higher N-alkanesmentioning
confidence: 99%
“…Calculations with the PR EoS (dashed lines) and RKPR EoS (solid line) correspond to quadratic mixing rules with null interaction parameters. Symbols: Experimental data from refs .…”
Section: Resultsmentioning
confidence: 99%